Dromia erythropus - Coelho, Petrônio Alves; Almeida, Alexandre Oliveira De; Bezerra, Luis Ernesto Arruda (Zenodo, 2008)
Dromia erythropus (George Edwards, 1771) Western Atlantic: Bermuda, Florida, Gulf of Mexico, West Indies, northern South America to Brazil (Santa Catarina). Central Atlantic: Ascension I. (Manning & Chace 1990; Melo & Campos Jr. 1999). Occurrence in northern and northeastern Brazil: FN: Viana et al. (2003b); AP: Silva et al. (1998); MA: Melo & Campos Jr. (1999); CE: Fausto Filho (1968); PE: Rathbun (1900); BA: Rathbun (1937). : Published as part of Coelho, Petrônio Alves, Almeida, Alexandre Oliveira De & Bezerra, Luis Ernesto Arruda, 2008, Checklist of the marine and estuarine Brachyura (Crustacea: Decapoda) of northern and northeastern Brazil, pp. 1-58 in Zootaxa 1956 (1) on page 7, DOI: 10.11646/zootaxa.1956.1.1, http://zenodo.org/record/5241063 : {"references": ["Manning, R. B & Chace, Jr., F. A. (1990) Decapod and Stomatopod Crustacea from Ascension Island, South Atlantic Ocean. Smithsonian Contributions to Zoology, 503, 1 - 91.", "Viana, G. F. S., Ramos-Porto, M., Travassos, P. E. P. F., Carvalho, G. (2003 b) Registro de Dromia erythropus (G. Edwards, 1771) para o Arquipelago de Fernando de Noronha, Brasil (Crustacea, Decapoda, Dromiidae). Boletim Tecnico-Cientifico do CEPNOR, Belem, 3 (1), 215 - 218.", "Silva, K. C. A., Ramos-Porto, M., Viana, G. F. S. & Cintra, I. H. A. (1998) Informacoes preliminares sobre os Brachyura (Crustacea: Decapoda) coletados na costa Norte do Brasil durante o Programa REVIZEE. Trabalhos Oceanograficos da Universidade Federal de Pernambuco, 26 (1), 85 - 97.", "Fausto Filho, J. (1968) Terceira contribuicao ao inventario dos crustaceos decapodos marinhos do Nordeste Brasileiro. Arquivos de Ciencias do Mar, 8 (1), 43 - 45.", "Rathbun, M. J. (1900) The decapod and stomatopod Crustacea. I. Results of the Branner-Agassiz Expedition to Brazil. Proceedings of the Washington Academy of Science s, 2, 133 - 156.", "Rathbun, M. J. (1937) The oxystomatous and allied crabs of America. Bulletin of the United States National Museum, 166, 1 - 278."]}